Exploring Students’ Creativity, Collaboration, and Communication Skills in Science Learning: A Descriptive, Correlational, and Cluster Analysis Approach - Dios Sarkity; Adam Fernando; Elfa Oprasmani; Trisna Amelia; Nevrita Nevrita; Yudi Pratama; M. Pemberdi Intasir (Universitas Lambung Mangkurat, 2026)
The aim of this study is to analyze students’ creativity, collaboration, and communication skills in science learning using a descriptive, correlational, and cluster analysis approach. This study used a non-experimental quantitative design involving 109 junior high school students in Tanjungpinang City. Data were collected using essay tests to measure creativity and observation sheets to assess collaboration and communication skills. Descriptive analysis, Spearman rank correlation, and K-means cluster analysis were used to analyze the data. The results showed that students' creativity and communication skills were generally in the moderate category, while collaboration had a relatively higher average score. Correlation analysis revealed no significant relationship between creativity, collaboration, and communication skills, suggesting that these three skills may not necessarily develop simultaneously across students in the present sample. Furthermore, the cluster analysis identifies three possible student profiles based on similarities in student skills, reflecting varying skill combinations and heterogeneity. These results indicate that the 21st-century skills development in science learning remains fragmented and requires more integrated learning strategies. This study provides benefits in designing learning environments where students' skills measured in this study are developed through adaptive and effective learning.